دراسة سريرية لتأثير استعمال الأجهزة الأكريلية المتحركة على انتشار النخور - حسن حازم; الخطيب سمير (Latakia University Journal -Medical Sciences Series, 2019)
يُعدُّ النخر السني من المشاكل المهمة التي يعاني منها المرضى حملة الأجهزة المتحركة. و من هنا كان الهدف من دراستنا هذه دراسة العلاقة بين استعمال الجهاز المتحرك و حدوث النخر السني. استخدمنا في دراستنا عينة مكونة من 350 مريضاً (198 ذكر و 152 أنثى) و قد تراوحت أعمارهم بين 18 – 70 سنة. لقد تم التأكد من أن هناك علاقة متناسبة طردياً بين النخر السني و استعمال الأجهزة المتحركة الأكريلية، بينما لم يكن هناك تأثيراً مهماً للجنس و التدخين في انتشار النخر السني. إن قلة العناية بالصحة الفموية و بالجهاز المتحرك، فضلاً عن تركه في الفم ليلاً في أثناء النوم، قد تم إثبات دورها بوصفها عوامل مهمة في زيادة احتمال نخر الأسنان المجاورة لهذه الأجهزة. Tooth decay is considered one of the most serious problems facing patients who wear removable appliances. Therefore, the objective of this study was to determine the relationship between the use of removable appliances and the occurrence of teeth decay. In this study, the sample used consisted of 350 patients (198 males and 152 females) aged between 18-70 years. This study maintained that there was a correlation between tooth decay and the use of removable appliances, whereas there was no significant effect of sex and smoking on the prevalence of decay. Moreover, lack of appliance and oral hygiene maintenance increased the likelihood of tooth decay.